Sprawozdanie z konferencji “Reformacja z perspektywy 500 lat Dzieje-Kultura-Społeczeństwo” - SMYK, Anita (Historia i Świat, 2018)
Overview and description of the Scientific Conference "Reformation from the perspective of 500 years. History-Culture-Society" at Siedlce University (2017.11.08)